TRANSFORMASI NILAI-NILAI PANCASILA DALAM PEMBAHARUAN HUKUM PIDANA NASIONAL - Ade Mahmud (Universitas Suryakancana, 2018)
The condition of the national criminal law as a legacy of the Dutch Colonial is deemed inconsistent with Pancasila values so that the effort to reform the criminal law (KUHP) continues to be voiced through the re-formulation of criminal law policy. The results (1) Renewal of national criminal law based on mission (a) Decolonization through